DETERMINATION OF THE LATERAL PRESSURE OF THE BACKFILL ON AGRAVITY-TYPE BERTHING STRUCTURE WITH A STONE PRISM OF IMPROVED FORM - Бугаєва, Світлана; Хонелія, Натела (SWorldJournal, 2024)
The paper examines a new design and technological solution for the construction of a gravity-type berthing structure using a new rational type of stone prism. The developed construction method provides the possibility of obtaining a vertical shape of a st